Studi Potensi Sumberdaya Andesit Menggunakan Metode Geolistrik Di Daerah Kokap, Kabupaten Kulonprogo, Daerah Istimewa Yogyakarta - Purwasatriya, Eko Bayu (Jenderal Soedirman University, 2013)
The study of andesite resources was carried out in Hargowilis village, Kokap sub-district, Kulonprogo regency, DaerahÂ Istimewa Yogyakarta province using geoelectrical data with Schlumberger configuration, as much as 14 point which is spreading onÂ 8 hectares area. Based on regional geological map of Yogyakarta area, study area include on intrusive rock lithologyâs unit composeÂ of hipersten andesite to augite-hornblende andesite and trachiandesite. Geoelectrical method is one of geophysical method that usedÂ to observed geological condition in subsurface based on rockâs electrical properties. Andesite is one type of igneous rock which haveÂ contrast electrical properties with its surrounding rock, generally sedimentary rocks, makes it suitable for geoelectrical method toÂ identify the presence of andesite in subsurface and also estimate its thickness to calculate the resources. Geoelectrical configurationÂ used is 1D Schlumberger configuration where this method have advantage more accurate to calculate the thickness of rock layerÂ especially in shallow area. The result of geoelectrical survey showing that it consist 2 layer of andesite, there are shallow layer andÂ deep layer. This result indicate that the igneous rock in study area not only intrusion type, but also lava flow type. ResourcesÂ potential of andesite both shallow and deep layer are 5,072,354 tons and resources potential of shallow andesite only is 3,162,566 tons.